CARIES AND ORAL HEALTH-RELATED QUALITY OF LIFE IN PEOPLE WITH SUBSTANCE USE DISORDER (SUD) AT DRUG REHABILITATION CENTRE LIDO, INDONESIA - Parorrongan, Chrisanty Anastasia; Theresia, Tiarma Talenta; Louisa, Marie; Effendi, Nadira Zahrani; Putri, Anzany Tania Dwi; Resthie Rachmanta Putri (Malaysian Journal of Public Health Medicine, 2025)
Substance use disorder (SUD) remains a significant issue in Indonesia. It impacts oral health, increasing the risk of caries, xerostomia, periodontal disease, and tooth loss. Untreated caries can lead to pain, discomfort, and anxiety, which lowers an individual’s quality of life. The concept that assesses how dental and oral health affect overall well-being is called Oral Health-Related Quality of Life (OHRQoL). This study examines the relationship between caries and oral health-related quality of life in individuals with SUD at the Lido Rehabilitation Center. It is an observational cross-sectional study involving 101 people with SUD, conducted in August 2024. Data were collected using the OHIP-14 questionnaire, which includes 14 questions across seven domains, and caries were assessed using the WHO index. The total score showed no significant correlation between caries and oral health-related quality of life (p=0.102). However, significant correlations were found in two OHIP-14 domains: psychological discomfort (p=0.047) and psychological disability (p=0.045). Overall, there is a relationship between caries and oral health-related quality of life among people with SUD at the Lido Rehabilitation Center, especially in the areas of psychological discomfort and disability.